Switching from trivalent to quadrivalent inactivated influenza vaccines in Uruguay: a cost-effectiveness analysis - Pablo Manuel Bianculli; Lucile Bellier; Ignacio Olivera Mangado; Carlos Grau Pérez; Gustavo Mieres; Luis Lazarov; Audrey Petitjean; Hugo Dibarboure; Juan Guillermo Lopez (Taylor & Francis Group, 2022)
We evaluated the cost-utility of replacing trivalent influenza vaccine (TIV) with quadrivalent influenza vaccine (QIV) in the current target populations in Uruguay. An existing decision-analytic static cost-effectiveness model was adapted for Uruguay. The population was stratified into age groups. Costs and outcomes were estimated for an average influenza season, based on observed rates from 2013 to 2019 inclusive. Introducing QIV instead of TIV in Uruguay would avoid around 740 additional influenza cases, 500 GP consultations, 15 hospitalizations, and three deaths, and save around 300 workdays, for the same vaccination coverage during an average influenza season. Most of the influenza-related consultations and hospitalizations would be avoided among children ≤4 and adults ≥65 years of age. Using QIV rather than TIV would cost an additional ~US$729,000, but this would be partially offset by savings in consultations and hospitalization costs. The incremental cost per quality-adjusted life-year (QALY) gained with QIV would be in the order of US$18,000 for both the payor and societal perspectives, for all age groups, and around US$12,000 for adults ≥65 years of age. The main drivers influencing the incremental cost-effectiveness ratio were the vaccine efficacy against the B strains and the percentage of match each season with the B strain included in TIV. Probabilistic sensitivity analysis showed that switching to QIV would provide a favorable cost-utility ratio for 50% of simulations at a willingness-to-pay per QALY of US$20,000. A switch to QIV is expected to be cost-effective for the current target populations in Uruguay, particularly for older adults.